Dinamika Kepercayaan Merek Dalam Era UGC : Peran Kualitas Informasi Terhadap Niat Beli Konsumen Digital - Ida Ayu Oka Martini; Anak Agung Putu Suryandari (Journal Research of Management, 2025)
This study investigates the impact of User-Generated Content (UGC) on consumer purchase intention by positioning Brand Trust as a mediating variable and Information Quality as a moderating variable. This research is motivated by the digital trust paradox, where the transparency of user-generated content can strengthen consumer trust in a brand, but simultaneously weaken it due to information overload and unverifiability. A quantitative approach was applied through an online survey involving 252 Generation Z respondents who actively use social media and engage with digital content. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) techniques. The findings revealed that UGC has a positive and significant effect on Brand Trust and purchase intention. Furthermore, Brand Trust positively influences purchase intention, emphasizing its psychological role in enhancing consumer trust and minimizing uncertainty in online purchasing decisions. The mediation effect of Brand Trust appears partial, indicating that UGC primarily drives purchase intention directly rather than through trust formation. Meanwhile, Information Quality was not found to significantly moderate the relationship between UGC and Brand Trust, indicating that consumers place more importance on the authenticity and emotional relevance of content than its technical accuracy. Overall, these results highlight that the credibility and social engagement embedded in UGC act as key drivers in building Brand Trust and driving purchase intent in today's digital environment.